Peran dan Tanggung Jawab Notaris Terhadap Pelaksanaan Pendaftaran Badan Hukum Perseroan Terbatas melalui Sistem AHU Online - Nur Alim, Bagas; Silaswaty Faried, Femmy; Suparwi, Suparwi (UNES Law Review, 2024)
The role of a Notary in the process of establishing a Limited Liability Company Legal Entity through the Online Legal Entity Administration System includes creating a deed of Establishment. Because making the deed is an act of a Notary in holding office, he or she must obey and submit to the Notary's Code of Ethics. The purpose of this research is to analyze and find out 1) What are the roles and responsibilities of a notary in establishing a limited liability company (PT) legal entity at the notary office Wahyu Analista, SH., M.Kn. The method used is juridical-empirical, relying on primary data from interviews and secondary data from literature. This research adopts a legislative approach by examining applicable legal regulations, including Law no. 2 of 2014 concerning Notary Positions and Law no. 40 of 2007 concerning Limited Liability Companies. The results of the research are: 1) The role and responsibilities of a notary include inputting data, making a deed of establishment, informing NPWP, domicile instructions, announcements in the State Gazette of the Republic of Indonesia, payment of PNBP, and inputting data for Ministerial Decrees. If there is a data error, the notary must compensate for the loss, correct the data, and make a deed of amendment in accordance with Article 1365 of the Civil Code.